Self-concept certainty in adaptive and maladaptive perfectionists. Issue 2 (29th April 2019) - Lo, Alice; Abbott, Maree J.
The present study examined the content of self-related beliefs (i.e., the self-concept) and the level of certainty associated with these beliefs (i.e., self-concept certainty) across adaptive and maladaptive dimensions of perfectionism. A sample of 103 university students (26 adaptive perfectionists, 28 maladaptive perfectionists, and 49 non-perfectionists) completed a series of questionnaires and a reaction-timed computer task assessing their self-concept content and level of self-concept certainty. Results revealed significant differences in the content of self-beliefs about personality attributes between perfectionist groups, such that those classified as adaptive perfectionists held more positive beliefs and less negative-related beliefs about their personality attributes when compared to maladaptive perfectionists. Results regarding self-concept certainty were less clear, with adaptive perfectionists being most certain in general on self-report measures, but more certain for positive personality attributes only when compared to maladaptive perfectionists on a reaction-timed decision-making task. Findings from the present study are discussed in terms of the way that self-concept certainty may differ across adaptive and maladaptive subtypes of perfectionists.